Factors that Influence Taxpayer Compliance with Tax Morale as an Intervening Variable: Faktor yang Mempengaruhi Kepatuhan Wajib Pajak dengan Moral Pajak sebagai Variabel Intervening - Selfia Sarumaha; Eliza; Elfiswandi (Perkumpulan Doktor Indonesia Maju, 2024)
Taxpayer compliance is a crucial factor in the success of a country's tax system. In Indonesia, the level of taxpayer compliance still needs to be improved. This study aims to analyze the factors that influence individual taxpayer compliance with a focus on the role of tax morale as an intervening variable. This study uses a quantitative approach with data collected from questionnaires distributed to individual taxpayers registered at KPP Pratama Padang Satu. Data analysis was performed using structural equation modeling. The results showed that the effectiveness of the tax system and tax sanctions had a positive and significant effect on taxpayer compliance. Interestingly, although trust in government has no direct effect on compliance, the effectiveness of the tax system is proven to be able to mediate the relationship between trust and compliance. Tax morale is also proven to mediate the positive effect of tax system effectiveness on taxpayer compliance. Increasing the effectiveness of the tax system and enforcing strict and consistent sanctions are key strategies in improving taxpayer compliance. In addition, efforts to build public trust in the government and improve tax morale through education and socialization also need to be a priority.